Developing The Capacity Building Model of Local Government in the Field of Digital-?Based Health - Santoso Haryono, Bambang (ExcelingTech, 2020)
Abstract Capacity building is a process carried out in a place / institution to make changes for the better so that the process that occurs can run according to the expectations and wishes of the community. In general, capacity building is an effort made to achieve good governance (good governance). The purpose of this research is to build a concept or some kind of guide that will be used by local governments in the health sector so that the performance of the government in carrying out health affairs, which consists of 14 objectives of the Malang city health office activities to be achieved in a year. The digital era is an era where everything in meetings is recorded electronically. The research model that will be used is to use a literature review by utilizing all health documents and several articles and books that can be used as supporting data. The result achieved is that the health office guidelines are used to reduce to a minimum the factors that hinder capacity building. The implication of this guideline is that there will be harmony or balance in running the government.